Indonesian Muslim Women: Between Culture, Religion, and Politics - Bani Syarif Maula (Ijtimā`iyya: Journal of Muslim Society Research, 2016)
Islam in Indonesia is culturally very different from that in the Middle East, particularly related to a tradition of greater freedom for women in public places. In Indonesia, there are many women entering public and political arena and even women are seeking and achieving unprecedented power and influence in public life. However, there are some barriers from religion and culture that give burdens to women to express their political views and to involve in public life. Very often women who want to enter politics find that the political and public environment is not conducive to their participation. This paper discusses cultural, religious, and political factors of the difficulties faced by Indonesian Muslim women to participate freely in public and political lives. This paper looks at how women’s status in cultural and social structure influences the involvement of women in political activities. This study is a philosophical investigation of the value of culture, religion, and politics to Indonesian women in democratic practices. With the use of intensive reading of books and other information sources, together with policy document analysis, the study aims to explore the problems and possibilities of putting the visions of democracy into practice in contemporary Indonesian women, to explore the nature of culture, religion, and politics in Indonesia in influencing women’s political activism, and to understand both the status of Muslim women and the dynamics of Muslim societies in Indonesia. This paper concludes that women are still under-represented in public and political institutions in Indonesia. The long struggle of women’s movement for equal rights has not been easy due to the cultural and religious reasons.